Dictates by the International Capitalism. Who Governs? - Noralv Veggeland (European Scientific Journal, ESJ, 2018)
The representative democracy has become weak and fragmented, and under control of international market policy approaches of national state governments and multilateral agreement organizations like the European Union. In this paper, I argue that any study and explanation of economic crises and their contemporary supranational governance structures solutions conducted in the democratic capitalism countries as USA during the last fifty years, must be anchored in a multidisciplinary context. Crises of the art are rooted in social structures and classes, and in the behavior of the capitalistic system, based on inequality and new classical economic theory and right-wing political ideology.